2021
DOI: 10.3390/ijerph18020491
|View full text |Cite
|
Sign up to set email alerts
|

A Mixed-Methods Systematic Review of the Impacts of Coronavirus on Society and Culture

Abstract: Little is understood of the social and cultural effects of coronaviruses such as coronavirus disease 2019 (COVID-19), severe acute respiratory syndrome (SARS) and Middle East respiratory syndrome (MERS-CoV). This systematic review aims to synthesize existing findings (both qualitative and quantitative) that focus on the social and cultural impacts of coronaviruses in order to gain a better understanding of the COVID-19 pandemic. Utilizing a predetermined search strategy, we searched CINAHL, PsycINFO, PubMed, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 45 publications
1
7
0
1
Order By: Relevance
“…The obtained results of the analysis confirm that the society underwent a panic (right and justified) (Islam et al, 2020;Yu, et al, 2021). Interestingly, an in-depth analysis of the received responses in relation to the characteristics of the respondents showed that significantly higher scores (in both parts of the questionnaire) were given by older people from smaller towns and with a lower social status.…”
Section: Resultssupporting
confidence: 57%
“…The obtained results of the analysis confirm that the society underwent a panic (right and justified) (Islam et al, 2020;Yu, et al, 2021). Interestingly, an in-depth analysis of the received responses in relation to the characteristics of the respondents showed that significantly higher scores (in both parts of the questionnaire) were given by older people from smaller towns and with a lower social status.…”
Section: Resultssupporting
confidence: 57%
“…This approach is needed to find a match in overcoming the growing problem of stigma. Yu et al 23 explain that understanding the socio-cultural conditions of the community is one important aspect in managing information so that the negative stigma against Covid-19 does not bias into a more serious problem. In different socio-cultural conditions, different handling is needed.…”
Section: Resultsmentioning
confidence: 99%
“…Aspects that affect the public stigma are important to be thoroughly studied so as not to make the situation worse during the pandemic. 22 The study of the Covid stigma is also important to find new methods of dealing with the circulating stigma, such as the art therapist proposed by Potash et al 19 or the behavioral approach pattern contained in the socio-cultural as studied by Yu et al 23…”
Section: Introductionmentioning
confidence: 99%
“…Pseudoscience, or a collection of beliefs or practices mistakenly regarded as being based on scientific methods, has emerged as a powerful destructive force during the current pandemic (45)(46)(47). Government intervention, or lack thereof, can drastically change the impact of the outbreak on society (48) and there is no better approach for a government than following the lead of science to take the most appropriate actions. Degraded trust and cohesion within a country are often shown to have large socio-economic impacts, they can also have dramatic consequences when compliance is required for collective survival (49).…”
Section: Apathetic Whole-of-government and Whole-of-society Approachmentioning
confidence: 99%